Insights into evolution mechanism of PAHs in coal thermal conversion: A combined experimental and DFT study. (1st May 2021) - Chen, Yi-Feng; Su, Sheng; Zhang, Liang-Ping; Jiang, Long; Qing, Meng-Xia; Chi, Huan-Ying; Ling, Peng; Han, Heng-Da; Xu, Kai; Wang, Yi; Hu, Song; Xiang, Jun
Abstract: The evolution mechanism and energy conversion of volatile in low-rank coal with pyrolysis temperatures still remain uncertain. The experimental results on gas products and light tar pyrolyzed from Shenfu coal at various pyrolysis temperatures reflect the complex correlation between volatiles and coal structure affected by temperatures. Thermodynamic competitive evolution towards CO from oxygen-containing structures are analyzed by density functional theory. The formation mechanisms of polycyclic aromatic hydrocarbons (PAHs) from by-product cyclopentadienyl through Diels-Alder reaction and C–H β -scission are confirmed at the CBS-QB3//M06–2X/def2-TZVP level of theory. Kinetic rate coefficients of the rate-limiting step are computed. Thermodynamic and kinetic calculation results indicate that phenols pyrolysis have to cross a higher energy barrier. Moreover, cyclopentadienyl thermodynamically tends to form indene at 645 °C, while forming PAHs such as naphthalene, even fluorene, phenanthrene, and anthracene at 855 °C, which is consistent with the experimental results. A hydrogen-rich environment can kinetically facilitate the formation of PAHs. Highlights: Correlations between coal structure, gas product and light tar are explored. Evolution pathways of CO and PAHs during coal pyrolysis are studied by DFT. Ether bridge and carbonyl could cleave to CO at 435 °C, while phenols at 645 °C. Cyclopentadienyl is an important intermediate to form PAHs. Kinetic study of PAHs with temperature is consistent with the experiment.